SOCIAL AND COMMERCIAL ISLAMIC FINANCE CONCEPTS - Daulay, Raihanah; Handayani, Susi (Proceeding International Seminar of Islamic Studies, 2024)
Islamic finance is a form of financial system that as a whole uses concepts and principles derived from the values contained in Islamic law, namely the Quran and Hadith. Islamic finance consists of commercial Islamic finance and Islamic social finance. Commercial Islamic finance is financial management that aims to get profit or profit by applying sharia values for human benefit. Islamic Social Finance is a form of implementation of social finance based on Islamic values that aims to provide benefits for the benefit of mankind as a whole. The Islamic financial system needs to be applied in every line of life that is able to prosper the community in general and expect blessings from Allah. Mudharobah is part of the commercial Islamic financial system. Zakat is the implementation of the running of Islamic social finance needed in providing benefits to the community as a form of running social values to improve the welfare of the people.